What determines the household intention of domestic waste separation? An application of Ajzen's theory of planned behavior - Muhammad Alif Haiqal Asmizar; Ilhamd Sazali; Nurul Hidayana Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2024)
Household waste is an integral part of human daily life. However, we often need to realize how important it is to correctly understand, manage, and recycle household waste. Household waste can include various types of waste items that are unwanted or can no longer be used, such as old mattresses, furniture, or broken electrical appliances. Household waste has negative impacts on the environment. This study examines the residents’ household intention of domestic waste separation among five main districts (i.e., Rembau, Kuala Pilah, Seremban, Rasah, and Nilai), in Negeri Sembilan, Malaysia. In this study, the Theory of Planned Behavior (TPB) is used which predicts three (3) elements will contribute to the subsequent intention to influence a person's behavior. The three elements are 1) attitude toward waste sorting behavior, 2) subjective norms, and 3) perceived behavioral control. This study adds two new variables, namely, policy and regulation, and facility support ensure the macro perspectives element being included in the model. Three hundred residents were selected through a cluster and convenience sampling method. The study used correlation analysis and multiple regression to test the research model. The study found significant correlations between attitudes toward waste sorting behavior, subjective norms, perceived behavioral control, policy and regulation, facility support, and household intention of domestic waste separation. The regression results also revealed that perceived behavioral control is the most significant predictor. The results of this study are expected to generate ideas and suggestions to improve household waste segregation practices that support recycling.